Effects of Braiding Parameters on Tissue Engineered Vascular Graft Development. Issue 24 (15th October 2020) - Zbinden, Jacob C.; Blum, Kevin M.; Berman, Alycia G.; Ramachandra, Abhay B.; Szafron, Jason M.; Kerr, Katherine E.; Anderson, Jennifer L.; Sangha, Gurneet S.; Earl, Conner C.; Nigh, Noah R.; Mirhaidari, Gabriel J. M.; Reinhardt, James W.; et al.
Abstract: Tissue engineered vascular grafts (TEVGs) using scaffolds fabricated from braided poly(glycolic acid) (PGA) fibers coated with poly(glycerol sebacate) (PGS) are developed. The approach relies on in vivo tissue engineering by which neotissue forms solely within the body after a scaffold has been implanted. Herein, the impact of altering scaffold braid design and scaffold coating on neotissue formation is investigated. Several combinations of braiding parameters are manufactured and evaluated in a Beige mouse model in the infrarenal abdominal aorta. Animals are followed with 4D ultrasound analysis, and 12 week explanted vessels are evaluated for biaxial mechanical properties as well as histological composition. Results show that scaffold parameters (i.e., braiding angle, braiding density, and presence of a PGS coating) have interdependent effects on the resulting graft performance, namely, alteration of these parameters influences levels of inflammation, extracellular matrix production, graft dilation, neovessel distensibility, and overall survival. Coupling carefully designed in vivo experimentation with regression analysis, critical relationships between the scaffold design and the resulting neotissue that enable induction of favorable cellular and extracellular composition in a controlled manner are uncovered. Such an approach provides a potential for fabricating scaffolds with a broad range of features and the potential to manufacture optimized TEVGs. Abstract : Tissue engineered arterial grafts are created from braided poly(glycolic acid) fibers at the boundaries of the manufacturable design space with and without poly(glycerol sebacate) coating and evaluated in a mouse intrarenal aortic model. Implants are followed with 4D ultrasound and explants are evaluated with biaxial mechanical testing and histological analysis.